On the governing dynamics of the VHF radar echoes from the mesosphere and collision-dominated lower E region over Gadanki (13.5°N, 79.2°E) - Selvaraj, D.; Patra, A.K.; Sathishkumar, S.; Kumar, K. Kishore; Rao, D. Narayana (My University, 2016)
In the present communication, the role of neutral dynamical processes in governing the morphology and seasonal variations of daytime VHF radar echoes from the mesosphere and the collision-dominated lower E region is discussed. While the seasonal variations of mesospheric echo occurrence show semiannual variation with their maxima in the equinoxes, the occurrence of E region echoes shows strong annual variation peaking in the summer with two secondary maxima identical to semiannual variation of the mesospheric echoes. The occurrence rates of the E region echoes, however, display year-to-year variability. Semiannual variations in the occurrence of low-latitude mesospheric echoes are closely linked with similar variations in the occurrences of temperature inversion, large wind shear, tides, and gravity wave activities in the same height region. In the case of E region echoes, the summer maximum and equinoctial secondary maxima are found to be linked with similar variations in wind and wind shear, Es activity, tidal, and gravity wave activities. Further, the summer maximum is found to be strongly correlated with that of meteor flux and nonmigrating diurnal tide. This finding is significant given the fact that such wind field in the presence of metallic ions could form both Es and field-aligned irregularities. The present results show that tides and gravity waves are the most important dynamical factors governing the morphology and seasonal variations of the mesospheric as well as lower E region echoes observed over Gadanki. These results are discussed in the light of current understanding on the dynamical coupling of the mesosphere and lower E region through tides and gravity waves.
Keywords: Mesosphere; Gadanki; Gravity wave; E region echo; Mesospheric echo; Tidal wave